PENINGKATAN AKTIVITAS BELAJAR MATEMATIKA SISWA KELAS VII MTSN1 KOTA BENGKULU DENGAN MODEL PEMBELAJARAN TALKING STICK - noviza, nelvi; fachruddin, muhammad; rusdi, rusdi (JP2MS, 2017)
This research aimed to find increased mathematic student learning activity in the first grade students of MTsN1 Kota Bengkulu which use talking stick teaching model. Type of this research is quasi experiment. This research conducted in MTsN1 Kota Bengkulu academic year 2016/2017. The sample was taken by purposive sampling technique so that VIIc taken as experiment class and VIIb as control class. During student learning looks very active discussion group then students enthusiastically follow the talking stick rolling accompany music. It was concludy that there was an increase in student learning activity of mathematic in the first grade students of MTs N1 Kota Bengkulu which use talking stick teaching model.Keywords: talking stick teaching model, activity